Increasing search engine's accuracy using links clustering (مجلة المنصور, 2023)
This study is devoted for searching free e-books problem because of itsimportance with spreading the e-libraries. When the web client asking for a freee-books the search engine returns selling e-books sites, this produce aconclusion of inaccuracy about this search engine. According to this case thisstudy suggest the philosophy of clustering a sample of web sites on thenumber of links which lead to the downloadable e-books and rank this siteshigher than the others with matching the entered keywords. Three clustershave been noticed (sites with high rank, sites with medium ranking, and lowranked sites).The proposed system (Ico.com) has been built form many components; thefirst is the web crawler which is a software Program for fetching data of webpages (like page address, subject, number of links…etc), the secondcomponent is the clustering program written using (VB6.0) language to clusterthe web pages databases according to the number of links to real existingdownloadable books, and the last component is the search engine interfacewhich is built using HTML and VB script under Active server pagestechnology. This work reached to increasing the search engine accuracy usingfactors like analyzing the number and the type of links by mining the web site’sdatabase to improve accuracy for search engines.